Oscilações não radiais e propriedades estelares globais de estrelas compactas anisotrópicas usando equações de estado realísticas - CURI, Elvis Johel Aquino (2022)
In this work, we have made a systematic study of how the gravitational wave frequency of the fundamental mode from compact stars is affected by anisotropic effects using realistic equations of state. Our study is an extension of the seminal research performed by Doneva [Phys. Rev. D 85 (2012) 124023], where a polytropic equation of state was used. To reach this objective, we considered compact stars which were built by using equations of state in the framework of a relativistic mean field theory for the case of hadronic stars and in the framework of the MIT model for the case of quark stars. In order to obtain some pertinent information that could give us the possibility to detect the anisotropy in compact stars, we also studied and analized the behaviour of various global stellar quantities, e.g., gravitational redshift, stellar mass, radius, among others. Additionally, we discuss anisotropic hybrid stars without mixed phase that are constructed using equations of state in the context of relativistic mean field theory (hadronic phase) and equations of state in the context of the Nambu-Jona-Lasinio (NJL) model (quarkionic phase). In this case, we study the behavior of the macroscopic quantities of mass and radius. We concluded that the anisotropic effects can have important consequences, which are strongly related to the anisotropic parameter and the equation of state of high density matter. Additionally, a comparison with observational data has been made and we have shown that the anisotropic parameter λ can be used as a tuning parameter to reproduce mass and radius observational data of neutron stars.